Articulation and Dynamics Influence the Perceptual Attack Time of Saxophone Sounds - Bechtold, Toni Amadeus; Senn, Olivier (Frontiers in Psychology, 2018)
Perceptual attack time (PAT) is defined as the moment when the most salient rhythmical feature of a sound is perceived. This paper focuses on the PAT of saxophone sounds, investigating how the location of this point in time changes when a note is played with different characteristics. Nine saxophone sounds that differ in articulation and dynamics were examined. Ground truth for PAT was determined in a synchronization judgment experiment with 40 participants. Articulation (p < 0.001, η2 = 0.316), dynamics (p < 0.001, η2 = 0.098) and their interaction (p < 0.001, η2 = 0.094) affected the placement of the PAT. The onset rise time, which has been used as a predictor for PAT in earlier studies, was only weakly correlated with PAT (r = 0.143, p = 0.006). The results further suggest that the PAT of a saxophone sound may be more successfully modeled as a probability distribution instead of an exact point in time, thus confirming previous findings.